Evaluasi Program Bursa Kerja (Job Fair) Dalam Penanggulangan Angka Pengangguran Di Kabupaten Sidoarjo - Tharisma Novitasari; Diana Hertati (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Sidoarjo district is one of the districts with the highest unemployment rate with total of 131,444 thousand people or in percentage of 10.97%. To overcome the problem of unemployment, the Sidoarjo Regency government has carried out various programs to overcome the unemployment rate, one of which is the Job Fair Program. This research includes qualitative research, and uses data collection techniques through interviews, observations, documentation, then qualitative data analysis is carried out through several stages, namely, data collection (Data Collection), data condensation (Data Condensation), data display (Data Display), and drawing conclusions or verification (Conclusion: drawing/verifying). The results and conclusions of the research are that the implementation of the Job Fair Program is quite effective, efficient, very helpful for the community in finding information related to vacancies in the company, the community's reach to the Job Fair program is evenly distributed, meets the needs of the community, is useful or valuable to the community and the Job Fair program is a strategic and preventive steps in overcoming the problem of unemployment. Although the company's target is still not optimal, it does not mean that the implementation of the Job Fair program has not been carried out properly.